Clinical similarity of the biosimilar ABP 501 compared with adalimumab after single transition: long‐term results from a randomized controlled, double‐blind, 52‐week, phase III trial in patients with moderate‐to‐severe plaque psoriasis4. (1st December 2017) - Papp, K.; Bachelez, H.; Costanzo, A.; Foley, P.; Gooderham, M.; Kaur, P.; Philipp, S.; Spelman, L.; Zhang, N.; Strober, B.
Summary: Background: ABP 501, a U.S.A. Food and Drug Administration‐ and European Medicines Agency‐approved biosimilar, is highly similar to adalimumab in structure, function and pharmacokinetics. Objectives: To demonstrate similarity in efficacy, safety and immunogenicity of ABP 501 vs. adalimumab for moderate‐to‐severe plaque psoriasis (clinical trial: NCT01970488). Methods: Patients were randomized (1 : 1) to receive ABP 501 or adalimumab 40 mg every 2 weeks for 16 weeks. At week 16, patients with ≥ 50% improvement from baseline in Psoriasis Area and Severity Index (PASI) score were eligible to continue to week 52. Patients receiving ABP 501 continued; adalimumab patients were rerandomized (1 : 1) to continue adalimumab or undergo a single transition to ABP 501. Key efficacy assessments included percentage PASI improvement from baseline, PASI responders and mean change in affected body surface area from baseline to weeks 16, 32 and 50. Safety was monitored via adverse events (AEs) and antidrug antibodies (ADAs) were assessed. Results: A total of 308 patients were rerandomized at week 16 (ABP 501/ABP 501, n = 152; adalimumab/adalimumab, n = 79; adalimumab/ABP 501, n = 77). PASI percentage improvements from baseline were similar across groups for weeks 16, 32 and 50 (range: 85·8–88·2%), with no significant differences detected across groups in percentages of PASI 50, 75, 90 and 100 responders. Changes from baseline in percentage body surface area affected were similar across groups and time points. No new safety signals were detected. AEs were balanced between groups. Percentages of patients with binding and neutralizing ADAs were similar across treatments. Conclusions: ABP 501 and adalimumab have similar clinical efficacy, safety and immunogenicity profiles over 52 weeks, including after single transition, in this patient population. Abstract : What's already known about this topic? Biosimilars can offer therapeutic alternatives for patients in need and are currently being developed for numerous diseases, including moderate‐to‐severe plaque psoriasis. ABP 501 is a U.S. Food and Drug Administration‐ and European Medicines Agency‐approved biosimilar to adalimumab and has been shown to be highly similar to adalimumab in structural, functional and pharmacokinetic evaluations. What does this study add? The current study demonstrates that ABP 501 and adalimumab are highly similar in clinical efficacy, safety and immunogenicity, including after single transition from adalimumab to ABP 501 treatment, in patients with stable moderate‐to‐severe plaque psoriasis. Plain language summary available online Respond to this article